Process of Democratization and Linguistic (Human) Rights in Nepal - Tumbahang, Govinda Bahadur (Tribhuvan University Journal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Nepal is a multi-ethnic and multi-lingual nation. However, the policies of one language, one culture and one religion adopted right from Prithvi Narayan Shah merely through Rana rulers to Panchayati rulers merely focused in consolidations power and sustaining dynasty rule deprived ethnic communities of their linguistic, cultural and religious rights. This article presents how ethnic communities were deprived of their linguistic rights and how they are gaining it after the restoration of multi-party democracy in 1990 and after the second people's movement in 2062/63 B.S. Tribhuvan University Journal Vol. XXVI, No. 1, 2009 Page: 7-16